Sound field simulation of the tractor’s gearbox structure using structural and acoustic interactions - PRIKRYL, K. (Archives of Acoustics, 1996)
The ANSYS 5.0 finite element software was used to develop a finite element for the determination of the sound field of the driving unit of a real tractor. Generally, noise from the gearbox structure is emitted through vibration on the product surface and it is necessary to predict correctly the sound field formed by this radiated noise. The sound field exterior environment was modelled with FLUID30 acoustic fluid elements. These elements are most useful for modelling the structural and acoustic interactions. The nodal acoustic pressures of the sound field are plotted as sound pressure contours. The Figures show the sound pressure contours near the vibrating surface and in the plane at the end of the investigated sound field. The paper deal with the modelling of the whole coupled structural-acoustic system of the gearbox in order to reduce the noise emitted from the vibrating surface.